A GENRE BASED APPROACH TO TEACHING WRITING AN EXPOSITION IN AN EFL CONTEXT(A Case Study at a Private University in West Java) - Dadan Jauhara, - (2010)
This study aims to investigate the teaching and learning of writing under the genre based approach to improve students' writing skills particularly in writing an Exposition text in a tertiary EFL context in Indonesia. This study employed a qualitative research design, embraced the characteristics of a case study and to some extent a program evaluation. This research was conducted in one private university in West Java employing multiple data collection techniques, particularly classroom observation by the researcher and his colleague, students' written journal on the teaching program, collection of sample students' texts, which were then analysed by using systemic functional grammar (SFG), and interview with the participants. The study reveals three findings related to the research questions. First, regarding the analysis of the students' texts, most of the students have shown a substantial progress in terms of schematic structure, social function, linguistic features and thematic progression. Second, most of the students respond to the teaching program positively. Third, there were some issues that emerged in the implementation of the teaching program, especially in the stage of joint construction, when the discussion in group was stuck and group members could not share their idea anymore. Finally, the solutions were proposed to solve the students' problems i.e. that the teacher should be more active and pay more attention to the groups which really need help and remind them that everyone has an equal right to contribute his/her idea in a group work. It is thus recommended that (1) the GBA be implemented in teaching writing to university students, and (2) the teaching of English grammar should be related to the teaching of writing or vice versa and explicitly should be focused on the aspects of language that enable students to use the language for different purposes and contexts.